THE INFLUENCE OF LEARNING MOTIVATION AND SELF-EFFICACY ON THE LEARNING INDEPENDENCE OF STUDENTS AT SMP NEGERI 3 PANCUR BATU - Salamah; Suryani Hardjo; Salamiah Sari Dewi (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
Independence as an element in the Pancasila student profile must be developed and possessed by every student to improve learning achievement. Learning independence is of course influenced by many factors. This research aims to analyze and determine the influence of learning motivation and self-efficacy on student learning independence. This research is a type of causal associative quantitative research. The research sample was 110 students in class VII and VIII of SMP Negeri 3 Pancur Batu. Research data was collected using a research scale that was declared valid and reliable. The data analysis technique uses multiple linear regression analysis. The research results show that: (1) there is a positive and significant influence of learning motivation on student learning independence, with a probability value of 0.000 <0.05; (2) there is a positive and significant influence of self-efficacy on student learning independence with a probability value of 0.000 <0.05; (3) there is a significant influence between learning motivation and self-efficacy on the learning independence of students at SMP Negeri 3 Pancur Batu. The assumption is that the higher the learning motivation and self-efficacy, the higher the student's learning independence, and the lower the learning motivation and the lower the self-efficacy, the lower the student's learning independence. The results of the coefficient of determination test show that the contribution or influence of learning motivation and self-efficacy simultaneously on student learning independence is 58.1%, while the remaining 41.9% can be explained by other variables outside the model or outside the variables proposed in the research.